Multi-locational evaluation of Linseed (Linum usitatissimum L.) germplasm under rainfed ecology: MULTI-LOCATIONAL EVALUATION OF LINSEED GERMPLASM - P K SINGH; R L SRIVASTAVA; RAM CHANDRA; SOHAN RAM; M P DUBEY; M K GHODKE; OM PRAKASH (Journal of Oilseeds Research, 2013)
Field experiments were conducted at three locations in augmented design during the winter season of 2008 allowed for the assessment of broad adaptation to dry and warm growing conditions of 100 linseed (Linum usitatissimum L.) accessions. Perusal of resultsrevealed that there exists sufficient genetic variability for seed yield in the studied linseed accessions. Sagar was adjudged best among the locationsfor harvesting a good yield. EC 704, an exotic line recorded highest seed yield at Sagar and Latur whereas, EC 1066, EC 1534 and EC 1466 recorded higher seed yield than the best check at all the three experimental sites showing a sign of wide adaptation. Such an approach to make efficient use of germplasm collections remains important even today. This contribution summarizesthat genotypes EC 704, EC 1066, EC 1534 and EC 1466 having stable yield potential may be exploited in the linseed breeding programme to combat global climate change.